Comprehensive monitoring of a special mixture of prominent endocrine disrupting chemicals in human urine using a carefully adjusted hydrolysis of conjugates - Denghel, Heike; Göen, Thomas (Analytical and Bioanalytical Chemistry, 2022)
Many xenobiotics were identified as possible endocrine disruptors during the last decades. Structural analogy of these substances to natural hormones may lead to agonists or antagonists of hormone receptors. For a comprehensive human biomonitoring of such substances, we developed a simple, reliable, and highly sensitive method for the simultaneous monitoring of the parameters bisphenol A, triclosan, methylparaben, ethylparaben, propylparaben, butylparaben, benzophenone-1, benzophenone-3, 3,5,6-trichloropyridin-2-ol, p-nitrophenol, genistein, and daidzein in urine. Thereby, optimization of the enzymatic hydrolysis and the use of β-glucuronidase from E. coli K12 as well as sulfatase from Aerobacter aerogenes ensures the acquisition of intact analytes without cleavage of ester bonds among parabens. Validation of the method revealed limits of detection between 0.02 and 0.25 µg/L as well as limits of quantification between 0.08 and 0.83 µg/L. Thereby, the use of analyte-free surrogate matrix for calibration and control material influenced the sensitivity of the procedure positively. Furthermore, excellent precision in and between series was observed. Good absolute and relative recoveries additionally proved the robustness of the multimethod. Thus, the procedure can be applied for exploring the exposome to these prominent endocrine disruptors in the general population. Graphical Abstract: [Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2022-12-02
Keywords: Conjugates; Endocrine disrupting chemicals; Enzymatic hydrolysis; GC-MS/MS; Human biomonitoring; Phenols

Determination of the UV absorber 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) and its oxidative metabolites in human urine by dispersive liquid-liquid microextraction and GC–MS/MS - Denghel, Heike; Göen, Thomas (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2020)
2-(2H-Benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) is an ultraviolet light (UV) absorber which prolongs the stability of plastics and other organic compounds towards UV radiation. Therefore, it is frequently used as a preserving additive and may result in an exposure of consumers. Thus, an analytical method using dispersive liquid-liquid microextraction and subsequent gas chromatography tandem mass spectrometry analysis with advanced electron ionization was developed for a human biomonitoring of UV 328 exposure, which enabled the determination of UV 328 and six of its metabolites in human urine. Sample preparation and derivatization were optimized. Baseline separation of the analytes was assured by the application of a suitable temperature program. The validation resulted in limits of detection of 0.1 µg/L for all analytes, variation coefficients from 1 to 12% for precision in series and from 5 to 12% for interday precision. Furthermore, relative recovery rates between 80 and 120% were determined. Moreover, the procedure was successfully applied to urine samples of a volunteer exposed to UV 328. The method showed excellent sensitivity, repeatability and robustness for all parameters and may be applicable for studies to elucidate the metabolism and kinetics of the investigated UV absorber and for monitoring of individuals with specific exposure to UV 328.
CRIS-Team Scopus Importer:2020-03-31
Keywords: Dispersive liquid-liquid microextraction; Human biomonitoring; Metabolites; Urine analysis; UV 328; UV absorber

Dispersive liquid-liquid microextraction (DLLME) and external real matrix calibration for the determination of the UV absorber 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) and its metabolites in human blood - Denghel, Heike; Göen, Thomas (Talanta, 2021)
2-(2H-Benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328; CAS: 25973-55-1) is a benzotriazole ultraviolet light (BUV) absorber which is applied to plastics and other organic substances to prevent discoloration and enhance product stability. Therefore, UV 328 is frequently used as a plastic additive and may lead to an exposure of consumers. For a reliable assessment of UV 328 metabolism, an analytical method applying dispersive liquid-liquid microextraction (DLLME) followed by gas chromatography tandem mass spectrometry and advanced electron ionization was developed which allows the determination of UV 328 and six of its metabolites in human whole blood. Sample preparation was optimized with respect to DLLME parameters. A critical aspect of the procedure was the application of spiked human blood for calibration, which proved to be essential for achieving accurate results. Validation of the method resulted in limits of detection of 0.1 μg/L for all analytes. Variation coefficients ranged from 2 to 9% for intraday precision and from 3 to 11% for interday precision. Furthermore, relative recovery rates between 80 and 100% were calculated. Afterwards, the procedure was successfully applied to blood samples collected from a volunteer orally exposed to a single dose of UV 328. The method proved to be highly sensitive, repeatable and robust for all compounds and may further be used for studies to elucidate the human metabolism and kinetics of UV 328 and for biomonitoring of specific, environmental and occupational exposure to this UV stabilizer.
CRIS-Team Scopus Importer:2021-01-01
Keywords: Dispersive liquid-liquid microextraction; Human biomonitoring; Metabolites; UV 328; UV absorber; Whole blood analysis

Human metabolism and kinetics of the UV absorber 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) after oral administration - Denghel, Heike; Hiller, Julia; Leibold, Edgar; Göen, Thomas (Archives of Toxicology, 2021)
2-(2H-Benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328; CAS: 25973-55-1) is an ultraviolet light (UV) absorber which belongs to the class of hydroxy phenol benzotriazoles. Therefore, UV 328 is added to plastics and other polymers due to its photostability to prevent discoloration and prolong product stability which may result in an exposure of consumers. However, information about the toxic effects on humans and the human metabolism are still lacking. In the present study, human metabolism pathways of UV 328 and its elimination kinetics were explored. For that purpose, three healthy volunteers were orally exposed to a single dose of 0.3 mg UV 328/kg bodyweight. UV 328 and its metabolites were investigated in blood and urine samples collected until 48 and 72 h after exposure, respectively. Thereby, previously published analytical procedures were applied for the sample analysis using dispersive liquid–liquid microextraction and subsequent measurement via gas chromatography coupled to tandem mass spectrometry with advanced electron ionization. UV 328 was found to be oxidized at its alkyl side chains leading to the formation of hydroxy and/or oxo function with maximum blood concentrations at 8–10 h after exposure for UV 328-6/3-OH, UV 328-4/3-OH and UV 328-4/3-CO. In contrast, a plateau for UV 328-4/3-CO-6/3-OH levels was reached around 10 h post-dosage. The highest blood levels were found for native UV 328 at 8 h after ingestion. Furthermore, biphasic elimination kinetics in blood were revealed for almost all detected metabolites. UV 328 and its metabolites did not occur in blood as conjugates. The renal elimination kinetics were very similar with the kinetics in blood. However, the prominence of the metabolites in urine was somewhat different compared to blood. In contrast, mostly conjugated metabolites occurred for renal elimination. In urine, UV 328-4/3-CO-6/3-OH was found to be the most dominant urinary biomarker followed by UV 328-6/3-OH and UV 328-4/3-OH. In total, approximately 0.1% of the orally administered dose was recovered in urine within 72 h. Although high levels of UV 328 in blood proved good resorption and high systemic availability of the substance in the human body, the urine results revealed a rather low quantitative metabolism and urinary excretion rate. Consequently, biliary excretion as part of the enterohepatic cycle and elimination via feces are assumed to be the preferred pathways instead of renal elimination.
CRIS-Team Scopus Importer:2021-07-09
Keywords: Human biomonitoring; Kinetics study; Oral application; UV 328; UV absorber

Oxidative phase I metabolism of the UV absorber 2-(2H-benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328) in an in vitro model with human liver microsomes - Denghel, Heike; Leibold, Edgar; Göen, Thomas (Toxicology in Vitro, 2019)
2-(2H-Benzotriazol-2-yl)-4,6-di-tert-pentylphenol (UV 328, CAS: 25973-55-1) is an ultraviolet light (UV) absorber which is used as an additive for plastics and other polymeric substances to prevent the host material from light induced degradation reactions. However, no information about human exposure, metabolism and kinetics is available for this substance so far. Therefore, in vitro experiments with human liver microsomes were performed to derive oxidative phase I metabolites of UV 328 in an explorative approach using liquid-chromatography coupled with tandem mass spectrometry. Initially, a suspect screening mode was applied to the incubated samples. Six metabolites with hydroxy or oxo groups as well as a metabolite carrying both hydroxy and carbonyl moieties at the alkyl side chains were postulated and custom synthesized as reference standards. Afterwards, the results were verified in a target screening approach. Thereby, five of the six investigated analyte structures were confirmed. Quantitative estimations of the generated transformation products revealed 2-(2H-benzotriazol-2-yl)-6-(3-hydroxy-2-methylbutan-2-yl)-4-(tert-pentyl)phenol (UV 328-6/3-OH), 2-(2H-benzotriazol-2-yl)-4-(3-hydroxy-2-methylbutan-2-yl)-6-(tert-pentyl)phenol (UV 328-4/3-OH) and 2-(2H-benzotriazol-2-yl)-4-(2-methylbutan-3-on-2-yl)-6-(3-hydroxy-2-methylbutan-2-yl)phenol (UV 328-4/3-CO-6/3-OH) as most promising parameters. In summary, oxidation of both alkyl side chains at the phenol moiety was proven, but no metabolic transformations at the benzotriazole moiety were observed.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Human liver microsomes; Identification of metabolites; Suspect screening; Targeted analysis; UV absorber

Simultaneous assessment of phenolic metabolites in human urine for a specific biomonitoring of exposure to organophosphate and carbamate pesticides - Denghel, Heike; Göen, Thomas (Toxicology Letters, 2018)
Organophosphate pesticides (OPP) and carbamates are still counted among the most prominent agents used for crops protection. Up to date the determination of dialkylphosphates and their thio derivatives in urine is established for the OPP biomonitoring. However, this approach does not provide information on the exposure to specific OPP agents. A lot of OPP as well as some carbamates also provide specific urinary biomarkers indeed. Analytical methods for the determination of phenolic metabolites of OPP and carbamates have already been established by different working groups. However, these approaches only acquire one or few analytes. Therefore, we developed an analytical procedure which enables the simultaneous assessment of a wide spectrum of phenolic metabolites of OPP, carbamates and other pesticides in human urine using GC-MS/MS. The method includes enzymatic hydrolysis, solid phase extraction, derivatization, and subsequent GC-MS/MS analysis. The method showed detection limits between 0.1 and 0.4 μg/l. Variation coefficients ranged from 1 to 9 % for precision in series and 1 % to 13 % for inter-day precision. Furthermore, recovery rates between 87 and 117 % were determined. Compared with other published analytical procedures, the present method enables the simultaneous monitoring of a much broader spectrum of pesticides and biocides whose structures contain aryl moieties with competitive or improved analytical reliability. Furthermore, the suitability of the developed procedure was verified through the successful application to urine samples of pesticide exposed humans.
EVALuna2:35247